Gastric toxicity involving alterations of gastritis-related protein expression in mice following long-term exposure to nano TiO2. (May 2017) - Hong, Fashui; Wu, Nan; Zhou, Yingjun; Ji, Li; Chen, Ting; Wang, Ling
Abstract: Nano TiO2 has been widely used in food industry as a coloring agent, whether the application has adverse effects on stomach for humans and animals is rarely concerned. This study determined whether intragastric administration with nano TiO2 every day for nine months cause gastric damages and dysfunction, and is associated with changes of stomach damage-related protein expression in mice. Our results suggested that nano TiO2 exposure resulted in significant titanium accumulation in the stomach, reductions in daily food intake and water intake, stomach weight, and stomach indices. Importantly, mice exhibited severe gastric damages such as gastric mucosa atrophy, erosion, inflammatory cell infiltration and cell morphologic damages including apoptosis, and coupled with reductions of serum pepsin activity, stomach total acidity and H + concentration, and increases of serum gastrin concentration and gastric pH. Furthermore, these are associated with decreased expression of IκB, TFF 1, 2, and increased expression of NF-κB, TNF-α, IL-lβ, -6, -8, COX-2, and PGE2 in the stomach. The findings showed that gastric toxicity of mice induced by chronic exposure to nano TiO2 may be associated with alterations of gastritis-related protein expression in mice. It implies that the potential adverse effects to digestive system health should be concerned. Graphical abstract: A schematic showing possible mechanisms of nano TiO2- induced damages of mouse stomach. Highlights: Nano TiO2 caused gastric lesions in mice. Nano TiO2 resulted in dysfunction of gastric secretion of mice. Nano TiO2 led to alterations of gastric inflammation signal pathway and transcription factor expressions.